2014
DOI: 10.1080/13691058.2014.924558
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among rural South African men: alcohol use, sexual decision-making, and partner communication

Abstract: Nearly one-third of South African men report enacting intimate partner violence (IPV). Beyond direct health consequences for women, IPV is also linked to varied risk behaviours among men who enact it, including alcohol abuse, risky sex, and poor health care uptake. Little is known about how to reduce IPV perpetration among men. We conducted retrospective, in-depth interviews with men (n=53) who participated in a rural South African program that targeted masculinities, HIV risk, and IPV. We conducted computer-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 54 publications
(60 reference statements)
5
66
0
Order By: Relevance
“…Two of the studies were based in South Africa, two in Uganda, one in Liberia and one in Thailand. Of the six studies, two described programmes that were designed to address IPV and CM jointly (Ashburn, Kerner, Ojamuge, & Lundgren, 2016;Hatcher, Colvin, Ndlovu, & Dworkin, 2014;Van den Berg et al, 2013); one was designed to address IPV, but reported unintended outcomes for CM (Abramsky et al, 2014(Abramsky et al, , 2016Kyegombe et al, 2015); and three were designed to address CM, but reported unintended outcomes for IPV (Cluver, Lachman et al, 2016;Cluver, Meinck et al, 2016;Sim, Annan, Puffer, Salhi, & Betancourt, 2014). Table 1 presents four studies which used a randomised controlled trial with a nested qualitative component: REAL Fathers in Uganda (Ashburn et al, 2015); SASA!…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of the studies were based in South Africa, two in Uganda, one in Liberia and one in Thailand. Of the six studies, two described programmes that were designed to address IPV and CM jointly (Ashburn, Kerner, Ojamuge, & Lundgren, 2016;Hatcher, Colvin, Ndlovu, & Dworkin, 2014;Van den Berg et al, 2013); one was designed to address IPV, but reported unintended outcomes for CM (Abramsky et al, 2014(Abramsky et al, , 2016Kyegombe et al, 2015); and three were designed to address CM, but reported unintended outcomes for IPV (Cluver, Lachman et al, 2016;Cluver, Meinck et al, 2016;Sim, Annan, Puffer, Salhi, & Betancourt, 2014). Table 1 presents four studies which used a randomised controlled trial with a nested qualitative component: REAL Fathers in Uganda (Ashburn et al, 2015); SASA!…”
Section: Resultsmentioning
confidence: 99%
“…Although the two fatherhood programmes in this review included components that address traditional gender norms in relation to caregiving, female caregiver involvement was minimal or absent (Ashburn et al, 2015;Hatcher et al, 2014;Van den Berg et al, 2013). There is growing recognition that fatherhood programmes need to work alongside efforts to support and protect women and children exposed to family violence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While we found that men were using moralising discourses and surveillance strategies to monitor women's behaviour and assess their relative risk of infection, over the course of the intervention we found that they increasingly expressed awareness of the need to reduce their own sexually risky practices and were more likely to report discussing the need for both partners to test for HIV (see also Hatcher et al 2014). This is consistent with the quantitative data from the same project reported by Coates et al (2014) and the qualitative findings reported by Maman et al (2014), which show increased rates of HIV testing over time.…”
Section: Discussionmentioning
confidence: 95%